IMPACT OF ALTERNATIVE DISPUTE RESOLUTION FOR JUSTICE DELIVERY IN NIGERIA: A STUDY OF PUBLIC COMPLAINTS COMMISSION ABUJA - Okoronkwo, Patience Nnenna (African Journal of Social and Behavioural Sciences, 2024)
This study examines the impact of alternative dispute resolution for justice delivery in the Public Complaints Commission, Abuja, Nigeria. A descriptive survey research design was adopted and the population of the study consisted of mostly public servants from the Federal Secretariat Abuja, a few business owners and adult students/lecturers. However, due to the large size of the entire population, it becomes reasonable for some proportion of the population to be selected to represent the overall population. Thus, two hundred respondents were targeted for the study while the Taro Yamane formula was used to determine 133 samples from the target population. In selecting respondents, a judgmental procedure was adopted. A questionnaire structured in Likert’s five-point scale was used for data collection. Data were analysed using simple percentages. Results revealed that all the means (continuous follow-up visits to offenders, ensuring proper collaboration between other agencies, engaging the duties of the police when necessary) employed by the commission, enforce its decision and recommendations. More so, findings further revealed that all the factors (provision of adequate funding, training programmes for officers, improvement in service condition, employment of qualified professionals in the commission) considered in this study affect the role of government in assisting the commission to discharge her duties. Based on the empirical evidence from the findings, the researcher recommends that the Commission should embark upon aggressive publicity of its activities, using electronic and print media. Such publicity must touch the rural communities, the public servants, the labour unions, the civil society organizations, to mention but a few. The Commission should endeavour to organize seminars or workshops for various Chief Executives of Public Organizations.